الهدي النبوي عند ظهور الأوبئة في ضوء الكتاب والسنة =The Prophet’s guidance when epidemics appear in the light of the Qur’an and Sunnah - Saeed, Khadiya Salem Mohammed; Mohammed Yaqub, Mohammed Abullais Shamsuddin (IIUM Press, 2020)
تناول البحث بيان الهدي النبوي حال ظهور الأوبئة الخطيرة، واستخدم في إعداد ها البحث المنهج الاستقرائي، والمنهج التحليلي. والنتائج التي توصل إليها أن الهدي النبوي يتضمن نوعين من الوقاية: الوقاية المعنوية والمادية، والوقاية المعنوية تتمثل في حث الله ورسوله  المؤمنين على التبين من الأخبار المتعلقة بالوباء والابتعاد عن الشائعات، وذكر أجور الأوبئة حتى لا يفوت الصبر على أقدار الله فيفوز بالأجر، والدعاء للمريض أمام الناس. وكان من هدي النبي  في حال البلاء بالأوبئة، أن جعل نظاما للوقاية المادية، يتضمن عزل المريض عن الأصحاء، وعدم الدخول إلى الأرض التي وقع فيها البلاء وعدم الخروج منها، وهو ما يعمل به الآن في العالم قاطبة. ومن هدي النبي  الوقائي المادي، المسارعة في طلب الدواء بالبحث والتحري وعن أفضل الأدوية والمطببين ووضع قواعد تلزم الأطباء بضمان صحة من يعالجونهم. ومن هدي النبي  في هذا المجال، استخدام وتجريب أكثر من علاج، وكان النبي  يقرن بين أكثر من علاج حتى يصل المرء إلى ما يناسبه من علاج، وتكرار جرعات العلاج حتى يبرأ المريض. ******************************** The research addressed the Prophet’s guidance in the emergence of serious epidemics, employing both inductive and analytical research methods. The research concluded that the Prophet’s guidance involves two types of prevention: moral and material preventio n. The former is demonstrated in different categories: 1), motivating the believers to investigate the news pertaining to the epidemic and to stay away from rumors, and 2), to mention the rewards of epidemic which leads to be happy with the destiny of Allah (SWT) which further helps to be success due to the reward, and 3), to pray for the patient in front of people.One of the Prophet’s (PBUH) guidance in the event of a epidemics outbreak was, to make a physical preservation, which includes isolating the p atient from the healthy people, and not entering the place where the disaster occurred and not leaving it, which can be observed in present situation across the globe. The guidance of the Prophet (PBUH) further consisted of materialistic precaution, which refers to seek the best doctors and medicine as quickly as possible, and to establish the rules which obligate the doctors to ensure the health of those who are under their treatment. In this regard, the guidance of the Prophet (PBUH) was to experiment more than one treatment, and He (PBUH) used to mix between more than one treatment until people got the appropriate treatment, and repeated doses until the patient acquitted.